Good Ethnic Minority Justice: The Need for Good Governance by Ethnic Minority Group - Awaludin Marwan, Awaludin Marwan (Jurnal Keamanan Nasional, 2019)
Good ethnic minority justice is a notion that stipulates equal treatment for all people, including ethnic minorities, regardless of their ethnic, religious, or cultural background. This paper will discuss the vital demand for the implementation of good governance in providing justice to ethnic minorities. Good governance, at least, comprises of the principle of transparency, the principle of participation, and the principle of human rights. Furthermore, this paper will focus on theoretical and philosophical analyses of the need for good ethnic minority justice. Some examples are mentioned from the situation of legal protection of ethnic minorities in Indonesia and the Netherlands. Meanwhile, philosophical discourses emphasize good ethnic minority justice which is the opposite of the dominant theory of justice. The theory of justice mostly supports the position of the majority. Good ethnic minority justice highlights the legal protection of ethnic minorities.